Impact of the pandemic disease on the Railway Central Traffic Control Centers - Šustr, Martin; Šohajek, Petr; Setlíková, Petra; Soušek, Radovan (Kaunas University of Technology, 2021)
Railway transport is the integral part of the transport system in the Europe, and also in the Czech Republic it is a part of the national critical infrastructure. For the railway operation are necessary both inanimate parts like railway lines and personnel such dispatchers. The train dispatcher, a human being as a part of the system which controls movements of the trains is very sensitive to diseases, especially during pandemics. The paper briefly describes current situation in the railway transport control of the Czech Republic, shortly deals with historical development which lead to the current situation and finally presents plans for the future. The paper shows weak points of operation control by the Central Traffic Control Centers and points out possible alternatives to eliminate these weaknesses and to prevent the impact of any severe diseases on the train operation.
Dopad pandemické choroby na Centrální dispečerská pracoviště
Keywords: dispatcher; pandemic disease; railway traffic control centers; train movement; dispečer; pandemická choroba; centrální dispečerská pracoviště; jízda vlaku